ANTIOXIDANT STATUS OF PRIMARY HOST PLANTS OF ANTHERAEA SP. - G. C. PATRA; N. MOHANTY; D. G. DE (The Bioscan, 2011)
The tropical tasar silkworm, Antheraea sp. feeds primarily on Shorea robusta (Sal), Terminalia tomentosa (Asan) and Terminalia arjuna (Arjun). As it has to counter the extremities of ecoclimatic conditions during its life cycle, to know the antioxidant source from outside, the antioxidant contents, like ascorbic acid (Vitamin C), glutathione and total phenolics including protein content of leaves of these host plants were estimated. Analyses showed that, among these three plants, Shorea is the best one containing highest antioxidant contents compared to the other two. So, Shorea is the highly recommendable feed for silkworm (Antheraea sp.) to increase the antioxidant status of the silkworm and thereby its silk productivity.